The Role of Social Interpersonal Communication on Abortion Decision Making: A Review of Literature. - Wahome, Mercy; Mberia, Dr Hellen K.; Sikolia, Dr Geoffrey (International Journal of Health, Medicine and Nursing Practice, 2017)
Purpose: The objective of the study was to role of social interpersonal communication on abortion decision making. Methodology: This study used a Desk top review. The analysis was largely based on literature review from previous surveys, program reports and internet search on secondary information relating to the social, interpersonal and communication. Results: From the reviewed literature, the study found out that sexual health education can help provide adolescents with decision-making information skills and Peer-reviewed programs, strategies, and resources for sexual health, mental and emotional health, injury prevention, tobacco and substance abuse, and exercise and healthy eating and issues of abortion. It was found out that programs which included knowledge, perceived risks, values, attitudes, perceived norms, and self-efficacy were found to be effective in guiding behavioural change. Adolescents showed that they are aware of the use of contraceptives but they are not easily accessible and the main reason for them to terminate the unwanted pregnancy was due to fear of rejection in the society and family. Worldwide, the most commonly reported reason women cite for having an abortion is to postpone or stop childbearing. The second most common reason - socioeconomic concerns - includes disruption of education or employment; lack of support from the father; desire to provide schooling for existing children; and poverty, unemployment or inability to afford additional children. In addition, relationship problems with a husband or partner and a woman's perception that she is too young constitute other important categories of reasons. Women's characteristics are associated with their reasons for having an abortion: With few exceptions, older women and married women are the most likely to identify limiting childbearing as their main reason for abortion. Recommendation: Since the findings of this study was based on literature review/desktop review, the study recommends for the use of semi structured questionnaires and unstructured interview guides to obtain both quantitative and qualitative data respectively. In so doing, it will enable the researcher to compare the findings with those obtained from the desk top review. This research recommends the use of Convergent Parallel research design to arrive at an integrated summary of the predictors (quantitative research), and views and personal experiences (qualitative research) on decision making on abortion.